Development of Risk-Based State-Owned Enterprises Performance Audit Framework to Enhance Company Value - Sinaga, Rudi Irwanto Hamonangan; Achsani, Noer Azam; Fahmi, Idqan; Wijaya, Chandra (Migration Letters, 2023)
In the face of fierce economic competition among State Owned Enterprises (SOE), encouraging each company to grow its corporate value through the development of a risk-based performance audit framework may be the best option for SOEs in Indonesia. SOE management can make ongoing improvements and respond rapidly to market changes by detecting company performance risks. The purpose of this research is to develop an SOE risk-based performance audit framework in order to increase company value. The Analytical Hierarchy Process (AHP) method was utilized to create an effective and efficient performance audit framework based on expert justification. The study’s findings indicate that the Supreme Audit Institution (BPK) strategy’s main priorities for the construction of the SOE risk-based performance audit framework include three important aspects: 1) synergy between BPK audits and SOE risk management and risk assessment by SOE internal auditors; 2) development and improvement of SOE risk management quality, and 3) effective risk assessment by SOE internal auditors. This strategy is supported by various major variables, including SOE risk management, risk assessment by SOE internal auditors, BPK audit scope, BPK audit standards, BPK audit guidelines, and BPK auditor competencies.